Evaluating the Performance of the Students of the Department of Geography at the College of Education According to Classroom Teaching Skills (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
To achieve this goal, a random sample of 25 male and female students was selected from the fourth stage students applied for the academic year 2022-2023.A research tool was also prepared represented by a note card that included the three main skills, which are the planning skill and includes eight sub-skills, the implementation skill and includes nine sub-skills and the evaluation skill and includes six sub-skills. After applying the tool and analyzing the data, the results showed that the applied students possessed the skill of planning and implementation to a medium degree, while the implementation skill was weak and in light of the results, a set of conclusions, recommendations and suggestions were presented.